Political Engagement, Skill Application and Creativity in Social Advocacy - Wei, Qin (Technium Social Sciences Journal, 2021)
Social advocacy is a core component and routine activity of social work. This paper focuses on several important elements in social advocacy. It discusses the necessity of political engagement in social advocacy, explores the application of advocacy skills with a case analysis of Wet’suwet’en solidarity advocacy of Indigenous Peoples, and examines the use of creative advocacy strategies in social work practice. It argues that a good social advocate should positively engage politics, effectively apply diverse and appropriate skills, and actively demonstrate creativity for achieving the advocacy aim and adjusting to the social change.